Parkinson’s Disease and SARS-CoV-2 Infection: Particularities of Molecular and Cellular Mechanisms Regarding Pathogenesis and Treatment - Aurelian Anghelescu; Gelu Onose; Cristina Popescu; Mihai Băilă; Simona Isabelle Stoica; Ruxandra Postoiu; Elena Brumă; Irina Raluca Petcu; Vlad Ciobanu; Constantin Munteanu (Biomedicines, 2022)
Accumulating data suggest that chronic neuroinflammation-mediated neurodegeneration is a significant contributing factor for progressive neuronal and glial cell death in age-related neurodegenerative pathology. Furthermore, it could be encountered as long-term consequences in some viral infections, including post-COVID-19 Parkinsonism-related chronic sequelae. The current systematic review is focused on a recent question aroused during the pandemic’s successive waves: are there post-SARS-CoV-2 immune-mediated reactions responsible for promoting neurodegeneration? Does the host’s dysregulated immune counter-offensive contribute to the pathogenesis of neurodegenerative diseases, emerging as Parkinson’s disease, in a complex interrelation between genetic and epigenetic risk factors? A synthetic and systematic literature review was accomplished based on the ”Preferred Reporting Items for Systematic Principles Reviews and Meta-Analyses” (PRISMA) methodology, including registration on the specific online platform: International prospective register of systematic reviews—PROSPERO, no. 312183. Initially, 1894 articles were detected. After fulfilling the five steps of the selection methodology, 104 papers were selected for this synthetic review. Documentation was enhanced with a supplementary 47 bibliographic resources identified in the literature within a non-standardized search connected to the subject. As a final step of the PRISMA method, we have fulfilled a Population-Intervention-Comparison-Outcome-Time (PICOT)/Population-Intervention-Comparison-Outcome-Study type (PICOS)—based metanalysis of clinical trials identified as connected to our search, targeting the outcomes of rehabilitative kinesitherapeutic interventions compared to clinical approaches lacking such kind of treatment. Accordingly, we identified 10 clinical trials related to our article. The multi/interdisciplinary conventional therapy of Parkinson’s disease and non-conventional multitarget approach to an integrative treatment was briefly analyzed. This article synthesizes the current findings on the pathogenic interference between the dysregulated complex mechanisms involved in aging, neuroinflammation, and neurodegeneration, focusing on Parkinson’s disease and the acute and chronic repercussions of COVID-19. Time will tell whether COVID-19 neuroinflammatory events could trigger long-term neurodegenerative effects and contribute to the worsening and/or explosion of new cases of PD. The extent of the interrelated neuropathogenic phenomenon remains obscure, so further clinical observations and prospective longitudinal cohort studies are needed.